Bartonella henselae Neuroretinitis in Patients without Cat Scratch - (:unkn) unknown (NATL INST INFECTIOUS DISEASES, 2018)
Cat scratch disease (CSD) is a syndrome characterized by lymphadenopathy, fever, and skin lesions following a cat scratch or bite. Bartonella henselae is the primary bacterial agent responsible for CSD. In this report, we describe cases with atypical presentation of serologically proven B. henselae neuroretinitis. In this study, 3 patients with neuroretinitis were evaluated. Animal contact histories; results of ocular examinations and systemic investigations; clinical findings; and treatment compliance of the patients were assessed. All patients denied history of contact with cats or other animals, and they did not have CSD findings. Serologic testing via indirect immunofluorescence assay (IFA) was used to diagnose Bartonella neuroretinitis. The IFA test results were positive for all patients. Two patients were treated with antibiotics. Optic disc edema and macular exudates resolved gradually, and at their last follow-up visits, all signs had disappeared. There was no disease recurrence after the completion of treatment. Serious complications were seen in the untreated patient. In conclusion, B. henselae infection should be considered even when there are no systemic signs and symptoms of CSD in patients with neuroretinitis.
Keywords: DISEASE; SPP.